2017
DOI: 10.1111/anu.12478
|View full text |Cite
|
Sign up to set email alerts
|

Dietary available phosphorus requirement for on-growing gibel carp (Carassius auratus gibeliovar. CAS III)

Abstract: A nine-week feeding experiment was conducted in flow-through system with gibel carp (43.8 ± 0.2 g) to study the effects of dietary available phosphorus (P) on growth, phosphorous digestibility and intestinal enzyme activities. Seven semipurified diets were formulated to contain 0.8 (the basal), 2.4, 3.6, 6.1, 7.4, 10.1 and 15.8 g available phosphorus kg −1 diet. The results showed that specific growth rate and feed efficiency increased with increasing dietary available P from 0.8 to 7.4 g P kg −1 . Fish body a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 45 publications
16
18
1
Order By: Relevance
“…The highest growth was observed in the D4 and D5 groups that received over 7.6 g/kg AP. This result was consistent with many previous results showing that reduced growth rate or feed utilization was the main deficiency signs of P (Borlongan & Satoh, ; Liang, Liu, Tian, Yang, & Liang, ; Luo, Tan, Liu, & Wang, ; Schamber et al., ; Shen et al., ; Wang et al., ; Xie et al., ; Yao et al., ; Ye et al., ). However, other researchers suggested that the growth of fish was not affected by different levels of dietary AP (Baeverfjord, Asgard, & Shearer, ; Chaimongkol & Boonyaratpalin, ; Fontagné et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The highest growth was observed in the D4 and D5 groups that received over 7.6 g/kg AP. This result was consistent with many previous results showing that reduced growth rate or feed utilization was the main deficiency signs of P (Borlongan & Satoh, ; Liang, Liu, Tian, Yang, & Liang, ; Luo, Tan, Liu, & Wang, ; Schamber et al., ; Shen et al., ; Wang et al., ; Xie et al., ; Yao et al., ; Ye et al., ). However, other researchers suggested that the growth of fish was not affected by different levels of dietary AP (Baeverfjord, Asgard, & Shearer, ; Chaimongkol & Boonyaratpalin, ; Fontagné et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Compared with other carps, the optimal AP of crucian carp was lower than that of gibel carp ( Carassius auratus gibelio var. CAS III) (10.7 g/kg) (Xie et al., ), similar to that of grass carp (8.6 g/kg) (Liang et al., ) and higher than that of common carp (5.5 g/kg) (Nwanna et al., ) and common carp (Jian) (5.2 g/kg) (Xie et al., ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, to minimize eutrophication of waterbody, aquafeeds should meet the P requirement of fish and avoid excess P contents in the diet at the meantime (Jokinen, Vielma, Aaltonen, & Koskela, ; Musharraf & Khan, ). The studies about P requirement and utilization have been largely reported in many fish species, such as large yellow croaker ( Pseudosciaena crocea R. ) (Mai et al, ), rainbow trout ( Oncorhynchus mykiss ) (Fontagné et al, ; Lellis, Barrows, & Hardy, ), juvenile black seabream ( Sparus macrocephalus ) (Shao et al, ), Africa catfish ( Heterobranchus bidorsalis ) (Nwanna, Adebayo, & Omitoyin, ), stinging catfish ( Heteropneustes fossilis ) (Zafar & Khan, ) and gibel carp ( Carassius auratus gibelio ) (Xie et al, , ), which, however, have rarely been studied in sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…and gibel carp (Carassius auratus gibelio) (Xie et al, 2017(Xie et al, , 2018, which, however, have rarely been studied in sturgeon.…”
mentioning
confidence: 99%